PENYEGARAN PENGETAHUAN KEBAHASAAN GURU BAHASA JERMAN KABUPATEN MALUKU TENGGARA - Serpara, Henderika; Karuna, Kalvin; Noya van Delzen, June Carmen (German für Gesellschaft (J-Gefüge), 2024)
Language skills including speaking, writing, listening, and reading are important aspects that must be mastered by a German teacher so that the learning process can take place effectively and thoroughly. This community service program aims to: (1) improve the professional competence of German language teachers in Southeast Maluku Regency; (2) expand the knowledge and understanding of German language teachers in Southeast Maluku Regency according to the European Common Reference Standard (GER); and (3) build networks and cooperation to create active and connected German language teachers, so that they can share experiences, resources, and best practices. This community service activity focuses on teachers' understanding of improving language skills, including listening, reading, speaking, and writing according to the European Common Reference Standards (GER). The method of implementing this community service activity includes several stages: (1) The preparation stage, which includes field coordination with partners, determining the schedule of activities, preparing training materials, and registering participants; (2) The implementation stage, which consists of interactive lectures through PPT presentations accompanied by question and answer sessions, responses, and training; (3) The reflection and evaluation stage, which is used to collect feedback on the entire learning process, both in terms of implementation and material achievement. The results of this service program show that the participants are satisfied with the material presented because it suits their learning needs and is able to improve their professional skills.